Evaluation of Dry Eye and Meibomian Gland Dysfunction With Meibography in Patients With Rosacea. Issue 5 (May 2015) - Palamar, Melis; Degirmenci, Cumali; Ertam, Ilgen; Yagci, Ayse
Abstract : Purpose: To evaluate the dry eye tests and meibography of patients with ocular rosacea. Methods: Thirty-six eyes of 18 patients with ocular rosacea (group 1) and 38 eyes of 19 healthy individuals (group 2) were enrolled. Besides full-eye examination, corneal and conjunctival fluorescein staining and Oxford scoring, tear film break-up time, Schirmer 1 test, ocular surface disease index score assessment, and evaluation of upper and lower eyelid meibomian glands using infrared captures of an optical coherence tomography (OCT) (Spectralis HRA+OCT; Heidelberg Engineering) device were performed (grade 0: no loss of meibomian glands, grade 1: gland dropout area <1/3 of the total meibomian glands, grade 2: gland dropout area 1/3 to 2/3 of the total meibomian glands, grade 3: gland dropout >2/3 of the total meibomian glands). Results: The mean ages of group 1 and group 2 were 50.2 ± 9.5 (range, 32–65), and 46.3 ± 14.1 years (range, 25–70), respectively ( P = 0.225). No significant difference in best-corrected visual acuity and meiboscores of upper eyelids were detected in between groups. Schirmer 1 and tear film break-up time in group 1 were significantly lower than in group 2 ( P = 0.005, P < 0.001, respectively). Ocular surface disease index and Oxford scale scores and meiboscores of lower and total (upper + lower) eyelids were significantly higher in group 1 than in group 2 ( P = 0.04, P = 0.018, P < 0.001, P = 0.03, respectively). Conclusions: Ocular rosacea causes dry eye and significant meibomian gland loss that can objectively be demonstrated with meibography. The infrared camera of OCT—that is widely found in many ophthalmology departments—might be used to evaluate meibomian gland dysfunction in these individuals.